Handwritable one-dimensional photonic crystals prepared from dendronized brush block copolymers. Issue 12 (18th February 2019) - Zhang, Tongzhou; Yang, Jixing; Yu, Xiaoliang; Li, Yuesheng; Yuan, Xiaoyan; Zhao, Yunhui; Lyu, Dong; Men, Yongfeng; Zhang, Ke; Ren, Lixia
Abstract : Second generation dendrons with six long alkyl groups and six benzyl groups as peripheral groups were modified into cis -5-norbornene- exo -2, 3-dicarboxylicanhydride to prepare dendronized monomers. Abstract : Second generation dendrons with six long alkyl groups and six benzyl groups as peripheral groups were modified into cis -5-norbornene- exo -2, 3-dicarboxylicanhydride to prepare dendronized monomers. Consequently, dendronized brush block copolymers (denoted as PNAM- b -PNBzM) were prepared by the sequential ring-opening metathesis polymerization of the two dendronized monomers. One-dimensional photonic crystals (1D PCs) from ultraviolet, visible to near infrared wavelength were rapidly fabricated by the direct solvent evaporation of the PNAM- b -PNBzM polymer solution owing to the big steric hindrance of the side chain dendrons. Interestingly, colorful letters have been handwritten using Chinese brushes with the tetrahydrofuran solution of PNAM- b -PNBzM as the "ink". The simple and convenient preparation of 1D PCs, especially the handwritable ones, showed great potential in reflective coatings as well as functional structural colors.